Eutrophication effects on CH4 and CO2 fluxes in a highly urbanized tropical reservoir (Southeast, Brazil) - Benassi, Roseli Frederigi; de Jesus, Tatiane Araujo; Coelho, Lúcia Helena Gomes; Hanisch, Werner Siegfried; Domingues, Mercia Regina; Taniwaki, Ricardo Hideo; Peduto, Thais Araujo Goya; da Costa, Danilo Oliveira; Pompêo, Marcelo Luiz Martins [UNESP]; Mitsch, William J (Springer Nature, 2021)
Shallow urban polluted reservoirs at tropical regions can be hotspots for CO2 and CH4 emissions. In this study, we investigated the relationships between eutrophication and GHG emissions in a highly urbanized tropical reservoir in São Paulo Metropolitan Area (Brazil). CO2 and CH4 fluxes and limnological variables (water and sediment) were collected at three sampling stations classified as hypereutrophic and eutrophic. Analysis of variance (ANOVA) and the principal component analysis (PCA) determined the most significant parameters to CO2 and CH4 fluxes. ANOVA showed significant differences of CO2 and CH4 fluxes between sampling stations with different trophic state. The hypereutrophic station showed higher mean fluxes for both CO2 and CH4 (5.43 ± 1.04 and 0.325 ± 0.167 g m−2 d−1, respectively) than the eutrophic stations (3.36 ± 0.54 and 0.060 ± 0.005 g m−2 d−1). The PCA showed a strong relationship between nutrients in the water column (surface and bottom) and GHG fluxes. We concluded that GHG fluxes were higher whenever the trophic state increases as observed previously in temperate and tropical reservoirs. High concentrations of nutrients in the water column in the studied area support the high production of autotrophic biomass that, when sedimented, ends up serving as organic matter for CH4 producers. These outcomes reinforce the necessity of water quality improvement and eutrophication mitigation in highly urbanized reservoirs in tropical regions. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Carbon dynamics; Eutrophication; Greenhouse gases; Phosphorus; Sanitation; Water management